Arah Politik Hukum Pengawasan Obat dan Makanan di Indonesia (Studi Harmonisasi dan Sinkronisasi Kelembagaan serta Kewenangan BPOM dan Kementerian Kesehatan) - Farina Firda Eprilia; Mei Susanto (Jurnal Interpretasi Hukum, 2025)
The aim of this research is to analyze the legal policy  of drug and food control in Indonesia. This is because drug and food supervision is the competence of BPOM but also needs to coordinate with the Ministry of Health. Apart from that, the issue of sectoral ego arises between the two when handling a case. The urgency of this research is to build and achieve compliance with public health. This research uses a normative juridical method using a statutory regulation approach, conceptual approach, case approach and comparative approach. In addition to photographing the existing conditions of drug and food supervision, this study can offer a type of legal policy for institutional arrangements between BPOM and the Ministry of Health so that they become synchronized and harmonious. In addition, this study also provides recommendations in the form of the need for joint regulations between BPOM and the Ministry of Health regarding overlapping drug and food supervision authorities. This study is expected to help improve drug and food supervision because it starts from the clarity of its legal policy accompanied by updates to regulations and authorities between institutions.